Pathway linking executive function problems and non-suicidal self-injury among adolescents: The mediating role of emotion dysregulation - Rachma, Aulia; Hendrawan, Donny (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2025)
Non-suicidal self-injury (NSSI) is a prevalent mental health issue among adolescents, with difficulties in emotional regulation identified as a significant predictor of such behavior. A set of neurocognitive skills known as executive function (EF) is also linked to NSSI. This study investigates the relationship between executive function problems and NSSI behavior, explicitly examining the mediating role of emotional dysregulation. Participants were selected using a non-probability purposive sampling technique, with the final sample consisting of 211 Indonesian adolescents aged between 12 and 18 (M = 14.57, SD = 1.42). The measurement instruments included the Teenage Executive Function Inventory (TEXI), the Cognitive Flexibility Scale (CFS), the Difficulties in Emotion Regulation Scale Short Form (DERS-SF), and the Deliberate Self-Harm Inventory (DSHI). Mediation analysis using the PROCESS macro for SPSS (model 4), revealed that emotion dysregulation significantly mediated the relationship between EF problems and NSSI. The indirect effect of EF problems and NSSI through emotion dysregulation was statistically significant (B = 0.203, 95% CI [0.0805, 0.3741]). Adolescents with lower EF are more prone to emotional difficulties, thus increasing the risk of NSSI. The study provides implications that help elucidate the dynamics of the NSSI phenomenon among adolescents. Furthermore, the findings highlight the need for interventions targeting both cognitive and emotional regulation skills to reduce NSSI in adolescents and promote overall mental health and well-being.